PENGARUH SEMANGAT KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG MANADO - Musak, AMELIA R; PIO, RIANE. JOHNLY; Tampi, REVO (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTThis study aims to determine the relationship of morale to employee productivity in the StateProperty Office and Auction Manado.This study used a quantitative descriptive method with simple correlation analysisapproach. In this study using two variables: the variable X and variable Morale Work ProductivityY. The data collection technique using a questionnaire or a questionnaire distributed to employees,the object of study observation and document study. Measurement of population in this study areemployees of the Office of the State Property and Auction services are 40 People Manadoemployees. Data were analyzed using product moment correlation formula, the coefficient ofdetermination and hypothesis testing significantly. To test the hypothesis used t test or partial test.Data were analyzed by manual calculation and use existing t table in the appendix.From the analysis we find the value of the product moment correlation coefficient of r = 0.827 whichshows that there is a positive relationship correlation r value of nearly (1,000) that can beinterpreted in the degree of relationship with work productivity morale at the high category. Thecoefficient of determination (R2) is equal to = 0.6839 or 68.39%, so as to have the sense that thevariables determining morale has power (influence) of 68.39% on the development of employeeproductivity, in other words that the development of morale is at 68.39% determined by the spirit ofthe work, while the remaining 31.61% is explained by other variables not examined in this study.Significance level of the coefficient on the real level test used was 1% (âˆž = 0.01). To test obtainedMorale thitung t = 9.067> t table = 2.429. It can be concluded that ho was rejected and Ha acceptedor Morale effect on Work Productivity of employees.Key word : spirit at work, produktivity